Bank Stability and Market Concentration: A Strategic Balance or an Inherent Risk in Indonesia? - Riani, Ririn; Ikhwan, Ihsanul (Islamic Economics Methodology, 2025)
This study aims to examine the impact of market concentration, internal bank characteristics, and selected macroeconomic variables on the stability of Indonesia's banking sector from 2015 to 2022, with a focus on the concentration-fragility and concentration-stability hypotheses. The research employs a sample of 47 commercial banks, including both conventional and Islamic banks, and uses the System Generalized Method of Moments (Sys-GMM) for empirical analysis. The results support the concentration-fragility hypothesis, indicating that increased market concentration negatively affects financial stability. Additionally, the study finds that lagged bank stability, profitability (ROA), capital adequacy (ETA), and operational efficiency (CIR) significantly contribute to current stability, while high Non-Performing Loans (NPLs) positively impact stability when risk management practices are effective. The findings are based on data from 2015 to 2022 and may not fully capture the long-term effects of market concentration on bank stability. Future studies should explore other emerging factors affecting banking stability. The study provides valuable insights for policymakers by emphasising the importance of regulatory frameworks that foster competition and strengthen internal controls to mitigate systemic risks.